A Markov Analysis of Surgical versus Medical Management of Chronic Migraines. Issue 5 (18th March 2022) - Yesantharao, Pooja S.; Lee, Erica; Klifto, Kevin M.; Colakoglu, Salih; Dellon, A. Lee; Reddy, Sashank K.
Abstract : Background: Refractory chronic migraine is a common and debilitating neurologic condition, affecting over 8 million people in the United States. It is associated with billions of dollars in lost productivity annually. Novel medical (anti–calcitonin gene-related peptide antibodies) and surgical treatment modalities have emerged for chronic migraine in recent years. The current study investigated the cost-utility of surgical versus medical management of refractory chronic migraine. Methods: A Markov cohort analysis using hybrid Monte Carlo patient simulation was performed to compare surgical decompression versus erenumab for the treatment of refractory chronic migraine in adults. Both societal and payer perspectives were considered. Primary model outcomes included incremental cost-effectiveness ratio, or cost per quality-adjusted life-year gained. Results: Over a 5-year period, migraine surgery was associated with an increase of 0.2 quality-adjusted life-year per patient when compared to erenumab. In terms of costs, the results demonstrated a 19, 337 decrease in direct medical costs and a 491 decrease in indirect costs (productivity lost) for the surgery cohort compared to erenumab. Because surgery improved quality of life and decreased costs compared to erenumab, even when considering revision surgery needs, surgery was the overall dominant treatment in terms of cost-effectiveness. Sensitivity analyses demonstrated that surgery was cost-effective compared to erenumab when patients required therapy for at least 1 year. Conclusions: Surgical deactivation of migraine trigger sites may pose a cost-effective approach to treating refractory chronic migraine in adults. This is especially the case when patients are anticipated to require therapy for more than 1 year.